Hydrates and polymorphs of lead squarate Pb(C4O4): Structural transformations studied by in situ X-ray powder diffraction and solid state NMR. (15th May 2019) - Bataille, Thierry; Bouhali, Amira; Kouvatas, Cassandre; Trifa, Chahrazed; Audebrand, Nathalie; Boudaren, Chaouki
Graphical abstract: The condensation of the crystal structure of lead squarate tetrahydrate subjected to dehydration is fully described. Depending on how fast the last water molecule is released, two polymorphs of lead squarate are obtained. Abstract: Considering the low dimensionality of the crystal structure of the known lead squarate tetrahydrate, Pb(C4 O4 )·4H2 O, the thermal reactivity of the powdered compound and structural studies of lower hydrates have been investigated from X-ray single-crystal and powder diffraction data, solid state NMR and thermal analyses. It is shown that Pb(H2 O)(C4 O4 ) and two polymorphs of anhydrous PbC4 O4 can be formed within different conditions. The departure of the water molecules leads to the condensation of initial inorganic chains into 2D or 3D-type crystal structures. The full decomposition of the squarate ligand provides successive lead oxides.